2012
DOI: 10.1517/17425247.2012.738664
|View full text |Cite
|
Sign up to set email alerts
|

Micro and nanosystems for delivering local anesthetics

Abstract: The design of novel drug delivery systems for local anesthetics must focus on how to achieve higher uploads of the anesthetic into the carrier, and how to sustain its release. This comprehensive review should be useful to provide the reader with the current state-of-art regarding drug delivery formulations for local anesthetics and their possible clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 124 publications
1
49
0
3
Order By: Relevance
“…In these lipid vesicles, formed by the hydrophobic effect to maximize the interaction between the acyl chains, protecting them from the contact with the aqueous medium, the hydrophobic tails turn towards the inside of the lamella and the polar heads are exposed outward, in contact with water [69]. Due to the presence of an aqueous compartment and lipid bilayers, liposomes can incorporate hydrophilic and hydrophobic molecules, which is quite interesting for a drug carrier [70].…”
Section: Liposomesmentioning
confidence: 99%
“…In these lipid vesicles, formed by the hydrophobic effect to maximize the interaction between the acyl chains, protecting them from the contact with the aqueous medium, the hydrophobic tails turn towards the inside of the lamella and the polar heads are exposed outward, in contact with water [69]. Due to the presence of an aqueous compartment and lipid bilayers, liposomes can incorporate hydrophilic and hydrophobic molecules, which is quite interesting for a drug carrier [70].…”
Section: Liposomesmentioning
confidence: 99%
“…Their glucopyranose units (6, 7, 8 for α, β and γ respectively) linked by α (1,4) linkages form a truncated cone with hydrophobic internal cavity, which accommodates hydrophobic drug moieties compatible with the cavity size (cavity size of 6.0–6.5 Å, in the case of β‐CD) . Regarding local anaesthetics, complexation with CDs has been shown to prolong the analgesia and decrease drug toxicity (see for a review). A recent study showed that OXZ‐γ‐CD complex largely improve OXZ aqueous solubility, but this type of CD is not recognised as safe for parenteral administration…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to pain relief, they produce side effects such as sedation, constipation, respiratory depression, euphoria, misuse, and addiction, which resulted in the opioid crisis. [17,18] Materials used for these structures are usually polyesters like polycaprolactone, polylactic acid, or poly(lactic-co-glycolic acid), and contain the local anesthetic either incorporated directly, or, in the case of the nanocapsules, dissolved in an oily core surrounded by the polymer. A prototypic κ-receptor selective agonist is U50,488H (U50), which has been shown to exert effective analgesia in animal pain models.…”
Section: Introductionmentioning
confidence: 99%